An Easy Synthesis of Two Steroid-Dihydropyrimidine Derivatives Using Three Components System - Figueroa-Valverde, Lauro; Diaz-Cedillo, Francisco; Garcia-Cervera, Elodia; Pool-Gomez, Eduardo; Rosas-Nexticapan, Marcela; Lopez-Ramos, Maria (Asian Journal of Chemistry, 2013)
In this study two new steroid-dihydropyrimidine derivatives were synthesized. In the first stage the route involved preparation of 6-(3-hydroxy-13-methyl-7,8,9,11,12,13,14,15,16,17-decahydro-6H-cyclopenta[a]-phenanthren-17-yl)-4-phenyl-3,4-dihydro-1H-pyrimidin-2-one (4) using estrone, benzaldehyde and urea in the presence of hydrochloric acid. The following stage was achieved by the reaction between pregnenolone, thiourea and benzaldehyde using as catalyst, hydrochloric acid to form the compound 6-[1-(3-hydroxy-10,13-dimethyl- 2,3,4,7,8,9,10,11,12,13,14,15,16,17-tetradecahydro-1H-cyclopenta[a]phenanthen-17-yl)-ethyl]-4-phenyl-3,4-dihydro-1H-pyrimidine-2-thione (7). The structure of all compounds was confirmed by spectroscopy and spectrometry data. In conclusion, in this study we report an efficient method for synthesis of two steroid-dihydropyrimidine derivatives using three components system. It is important to mention that the method used is highly versatile and the yield is good.